Ocena pracowników w procesie zarządzania personelem na przykładzie Urzędu Gminy Korzenna - Kmak, Lidia (My University, 2013)
Celem pracy było omówienie jednego z elementów zarządzania personelem, którym jest system ocen pracowników. System ten został przedstawiony na przykładzie Urzędu Gminy Korzenna. Badanie przeprowadzono wśród pracowników urzędu w postaci ankiety oraz podjęto próbę analizy jego wyników. Stwierdzono wady stosowanego systemu oceniania i zaproponowano pewne usprawnienia.

The aim of this project was to present an employee appraisal system which constitutes one of the elements of personnel administration. This system was demonstrated by the example of the Municipal Council in Korzenna (Urząd Gminy Korzenna). A survey was conducted among employees of the Municipal Council who were asked to complete a questionnaire. The results of the survey were analysed. Drawbacks of this system were confirmed and certain improvements were proposed.
Employees appraisal system in the process of personnel administration demonstrated by the example of the Municipal Council in Korzenna
Keywords: zarządzanie zasobami ludzkimi; ocenianie; metody oceniania; błędy w ocenianiu; kryteria oceniania; zasady oceniania; rozmowa oceniająca; human resources management; appraisal; methods of an appraisal; mistakes in an appraisal; criteria of an appraisal; principles of an appraisal; appraising interview